2017
DOI: 10.5194/esd-2017-90
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hazards of decreasing marine oxygen: the near-term and millennial-scale benefits of meeting the Paris climate targets

Abstract: Abstract. Ocean deoxygenation is recognized as key ecosystem stressor of the future ocean and associated climate-related ocean risks are relevant for policy decisions today. In particular, benefits of reaching the ambitious 1.5• C warming target mentioned by the Paris Agreement compared to higher temperature targets are of high interest. Here, we model oceanic oxygen, warming, and their compound hazard in terms of metabolic conditions on multi-millennial timescales for a range of temperature targets. Scenarios… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Deoxygenation peaks at year A.D. 4000 when deep water had sufficient time to age, to accumulate remineralized nutrients, and to integrate losses by oxygen consumption. In addition, warming causes O 2 loss due to changes in solubility (see also Battaglia & Joos, 2017 for process attribution).…”
Section: Transient Circulation Changes Export Production and Deoxygmentioning
confidence: 99%
“…Deoxygenation peaks at year A.D. 4000 when deep water had sufficient time to age, to accumulate remineralized nutrients, and to integrate losses by oxygen consumption. In addition, warming causes O 2 loss due to changes in solubility (see also Battaglia & Joos, 2017 for process attribution).…”
Section: Transient Circulation Changes Export Production and Deoxygmentioning
confidence: 99%
“…They attributed this potential reoxygenation of the tropical ocean thermocline to intensified ventilation that kicked in their simulation after 2150 and to a decline in tropical export production leading to reduced biological O 2 consumption in the underlying thermocline. In the deep ocean, several studies suggested a recovery of deep ocean O 2 levels under multimillennial global warming scenarios (Battaglia & Joos, 2018; Ridgwell & Schmidt, 2010; Schmittner et al, 2008; Yamamoto et al, 2015). In all of these models, the recovery was caused by a millennial‐scale emergence of a more vigorous deep ocean ventilation under protracted global warming.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics of the dissolved oxygen in the ocean has been attracting considerable attention over the last decade [8,9,[22][23][24]. The existing observations point out at a gradual decrease of the average oxygen level across the globe, with the areas of extreme conditions (a severe lack of oxygen resulting in anoxia and mass mortality of the marine fauna) being fast growing in size.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%